2004
DOI: 10.1002/pd.826
|View full text |Cite
|
Sign up to set email alerts
|

QF‐PCR‐based prenatal detection of aneuploidy in a southeast Asian population

Abstract: The QF-PCR methodology is an efficient cost-effective method of screening for major chromosome aneuploidy, and, for certain referral categories, could be used alone. It also appears to be applicable to patients of different ethnic origins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…As this approach has developed, it has been widely used in numerous countries for >10 years and has proved to be an accurate, less labor-intensive and robust prenatal test for chromosomal aneuploidies (3,4,(6)(7)(8)(9)(10). One of the most evident advantages of QF-PCR is the automation of the procedure, allowing a high throughput of samples at a low cost.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As this approach has developed, it has been widely used in numerous countries for >10 years and has proved to be an accurate, less labor-intensive and robust prenatal test for chromosomal aneuploidies (3,4,(6)(7)(8)(9)(10). One of the most evident advantages of QF-PCR is the automation of the procedure, allowing a high throughput of samples at a low cost.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported the application of QF-PCR in the prenatal diagnosis of common chromosomal aneuploidies, the majority of the markers used were based on a Caucasian population and were not suitable for a Chinese population (3,4,(6)(7)(8)(9)(10). Furthermore, few studies have investigated the polymorphisms of STR markers on chromosome 13 (4,7,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Americans have lower heterozygosity at the locus D18S391 (0.75), whereas they have higher heterozygosity at the two loci P39 and DXS8377 (0.87 and 0.95, respectively) (Brown et al, 2006). But, in a Southeast Asian population, Quaife et al (2004) reported that the heterozygosity for D18S391 was as low as 0.61. Gole et al (2008) reported that among the Asian ethnic groups, the Chinese showed a higher heterozygosity index for X22 (90%) as compared to the Indians (72.7%) and Malays (66.6%).…”
Section: Introductionmentioning
confidence: 99%
“…These abovementioned characteristics explain the wide application of STRs in forensic individual identification, prenatal and postnatal diagnosis of chromosome aneuploidies, and paternity testing (Mansfield, 1993). STR markers demonstrating two peaks are heterozygote and are known as informative markers and those demonstrating only one peak are homozygote and are known as uninformative markers (Andonova et al, 2004;Quaife et al, 2004). In order to perform a reliable and accurate QF-PCR assay, a minimum of two heterozygote markers per chromosome are required to confirm the copy number of the chromosome of interest (Association for Clinical Cytogenetics and Clinical Molecular Genetics Society, 2012).…”
Section: Introductionmentioning
confidence: 99%